2016
DOI: 10.1007/s10068-016-0141-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic effect of quercetin-rich onion peel extract in C57BL/6J mice fed with high cholesterol diet

Abstract: Onion peel (OP) extract is known as a rich source of flavonoids, mainly quercetin. We hypothesized that OP has hypocholesterolemic effects. To investigate the effect of OP, C57BL/6J mice were divided into 4 dietary groups (=10); normal diet (ND); high cholesterol diet (HC); and high cholesterol diet with 100 or 200 mg OP extract (OP-100 or OP-200, respectively) per kg of body weight. After 12 weeks, lower values of liver weight, serum total cholesterol levels, LDL cholesterol, atherogenic index, cardiac risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This result was in agreement with Kang et al . (); who observed the liver weight gain in mice fed with HCD. Furthermore, the increase of epididymal and perirenal adipose tissue weight was also observed in HC group, which was connected with the increasing body mass as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…This result was in agreement with Kang et al . (); who observed the liver weight gain in mice fed with HCD. Furthermore, the increase of epididymal and perirenal adipose tissue weight was also observed in HC group, which was connected with the increasing body mass as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Serum lipid analysis was performed as described previously (Kang, Pichiah, Abinaya, Sohn, & Cha, 2016). Serum concentrations of TC, TG, HDL‐C, and LDL‐C were determined using commercial assay kits (Nanjing Jiancheng Bioengineering Institute).…”
Section: Experiments Methodsmentioning
confidence: 99%
“…Altogether, these studies demonstrated that Qu may be a promising drug for the treatment and prevention of atherosclerosis in ASCVD. Wistar rats Elevate activity of hepatic CYP7A1, LXRα, and ABCG1 to promote cholesterol-to-bile acid conversion and cholesterol efflux [114] C57BL/6J mice Upregulate LDLR and CYP7A1 gene expression to facilitate the removal of cholesterol via fecal excretion [115] Wistar rats…”
Section: Elimination Of Etiology Reduction Of Complications and Effmentioning
confidence: 99%